Growth and Poverty: Lessons from the East Asian Miracle Revisited - M. G. Quibria (Asian Development Bank Institute (ADBI), 2002)
This paper provides an extensive review of growth, inequality and poverty reduction in the East Asian miracle economies. This review suggests that the basic impetus for poverty reduction was robust economic growth, which was fostered by a conducive policy and institutional framework. This framework-—which helped to create a “level playing field”—encouraged high investment, production over diversion, and efficient use of investible resources.
hdl:11540/4139
Keywords: 330